THE IMPACT OF AGROTOURISM DEVELOPMENT ON THE SOCIAL ECONOMIC LIFE OF LOCAL COMMUNITY KAMPUNG FLORY SLEMAN, YOGYAKARTA - Ni Made Sri Puspa Dewi Roels (Journal of Tourism Destination and Attraction, 2020)
This research was conducted in Flory Village, Tridadi Village, Sleman, Yogyakarta. Flory Village has three main destinations which are divided into three zones, namely Taruna Tani Zone, Bali Ndeso and Flory Tourism Village. Flory Village has been developed in the last six years and continues to experience rapid development. The focus of this research is about the impact of developing agrotourism on the economy of local communities. Agrotourism is the Taruna Tani Zone which is managed by the local community. The study used a descriptive qualitative research approach with data collection using in-depth interviews, observation and documentation. Data analysis methods used are interactive models, such as: data collection, data reduction, data presentation and drawing conclusions. The results of this study are that local communities have a positive impact on the development of agrotourism. Kampung Flory is managed by young people who have skills in farming. The young people who initially did not know where to market their farm products, became have a place to share knowledge and also get income. The plants then distributed to consumer sand also get income from tourists who visit. The community not only got benefits from being professional farmer in Kampung Flory, but also as many who can open a food stall business around the agrotourism area. Agrotourism development also provides the benefits of knowledge in the form of skills for farming so that it can increase the community's economy. Agrotourism exists as a place for the community to channel farming hobbies and can also provide education to tourists.